Nomads and networks the ancient art and culture of Kazakhstan - Stark, Soren; Rubinson, Karen Sydney 1943-; Samashev, Z. S. (Zainolla Samashevich); Chi, Jennifer; Alimbai, Nursan ([New York] Institute for the Study of the Ancient World, 2012)
Presents an unparalleled overview of the sophisticated culture of pastoral nomadic populations who lived on the territory of present-day Kazakhstan from roughly the middle of the first millennium BCE to the early centuries CE.--Book Jacket.
The roots of Iron Age pastoral nomadic culture / Nikolay A. Bokovenko and Zainolla S. Samashev -- The Berel Kurgans: some results of investigation / Zainolla S. Samashev -- Results of multidisciplinary studies and reconstructions of materials from the Baigetobe Kurgan at Shilikty / Abdesh T. Toleubaev, Al-Farabi Kazakh -- Some questions regarding the rock art of Kazakhstan / Sagynbay Myrgabayev -- Burial practices and social roles of Iron Age mobile pastoralists / Karen S. Rubinson -- Mounted warfare and its sociopolitical implications / Bryan K. Hanks -- Nomads and their networks: elites and their connections to the outside world / Sören Stark -- Cycles of Iron Age mobility and sedentism: climate, landscape, and material culture in southeastern Kazakhstan / Claudia Chang -- Society and culture of the nomads of central Asia through time / Nursan Alimbai.
Catalogue from the exhibition held at the Institute for the Study of the Ancient World at New York University, March 7-June 3, 2012.
Includes bibliographical references.
Keywords: Decorative arts -- Kazakhstan -- History; Decorative arts -- Kazakhstan -- History -- Exhibitions; Kazakhstan -- Antiquities; Kazakhstan -- Antiquities -- Exhibitions